Hubungan Nilai-Nilai Islami, Budaya dan Kinerja Sumber Daya Insani Bank Muamalat Indonesia - Poppy Novita Pasaribu; Musa Hubeis; Endang Gumbira Said; Aji Hermawan (Institut Pertanian Bogor, 2011)
The objective of this reseach is to find out these following matters: the influence of pray essential toward the work culture, the influence of work culture toward human resource (HR) performance, the influence of pray essential toward HR performance and the indirect influence of pray essential toward HR performance in work culture. This study takes place in Bank Muamalat Indonesia (BMI). Respondents are collected by purposive sampling method. Data collection through questionnairy with Likert scale and literature study. Data analysis used for this research is Stuctural Equation Modeling (SEM) technique. Factors of pray essence consist of 6 (six) variables, they are concentrate, understanding, respect, terrified and adore, hope for mercy and bless and embaress for carelessness. Factors of work culture are individual initiative, risk job tolerate, supervision, integration, management support, control, identity, compensation, conflict toleration and communication pattern. Factors of HR performance are job knowledge, job quality, initiative, teamwork, absence and time resource responsibility. The results show, there is a significant influence of pray essential toward work culture, there is a significant influence of work culture toward HR performance, there is a significant influence of pray essential toward HR performance, and there is no direct influence of pray essential, based on work culture toward HR performance. By understanding the variables that influences BMI pray essential, work culture and HR performance, the stakeholders can use the information to make improvement to gain sustainaibility of business